The Effects of the "War on Science" Frame on Scientists' Credibility. Issue 1 (February 2019) - Hardy, Bruce W.; Tallapragada, Meghnaa; Besley, John C.; Yuan, Shupei
A randomized experiment of 1, 024 U.S. adults was conducted to examine the effect of the war on science frame on perceptions of scientists' credibility. Because recent use of this frame is a response to the Trump Administration, those who politically align with him (e.g., conservatives) are likely to experience identity threat when confronted with the war on science frame. Results show that when viewed as aggressive, the war on science frame prompted conservatives to report lower agreement with a scientist credibility index than liberals, suggesting that the war on science frame has the potential to further polarize science.